Does tourism impact aquatic insects in a high altitude stream? - Bispo, Carlos Antonio; Lourenço, Anete Pedro; Garraffoni, André Rinaldo Senna (EntomoBrasilis, 2015)
Human activity often has a negative effect on stream quality and the biodiversity of aquatic fauna. The present study investigated the distribution patterns of aquatic insect populations in the Sentinela stream in Biribiri State Park, Diamantina, Minas Gerais, Brazil, and we correlated the patterns to possible impacts caused by tourists. We sampled the aquatic insect population few days before and few days after the holidays and monthly during the year. Fifteen groups of samples were taken from January through December 2011 at four different sites. For each site, three sub-samples were taken by drifting the entomological net and disturbing the substrate using the kick method. 3601 individuals were collected, and 8 orders and 41 families were identified. Environmental indices showed excellent water quality for sites 1 and 2, which are minimally affected by tourism and average water quality for sites 3 and 4, which are highly impacted by tourism. Three of the four holiday periods analyzed showed a significant decrease in insect abundance after the holiday. The richness and diversity of the aquatic insect fauna did not show seasonal fluctuations, despite differences in stream flow velocity during the dry and rainy periods. Our results indicated that the disturbances caused by tourism affect directly the diversity and abundance of aquatic insects in the Sentinela stream. In addition, these insects were suitable for the evaluation of human impacts caused by tourism in the conservation of freshwater ecosystem. O Turismo Impacta os Insetos Aquáticos em um Riacho de Alta Altitude? Resumo. A atividade humana tem afetado negativamente a qualidade dos ambientes lóticos e a biodiversidade da fauna aquática. O presente estudo investigou os padrões de distribuição das populações de insetos aquáticos no córrego Sentinela no Parque Estadual do Biribiri, Diamantina, Minas Gerais, Brasil, e correlacionou esses padrões com possíveis impactos causados pelas atividades do turismo. As populações de insetos aquáticos foram amostradas alguns dias antes e alguns dias após dos feriados e mensalmente durante o ano, totalizando quinze amostras entre os meses de janeiro e dezembro de 2011 em quatro locais diferentes. Para cada local, foram realizadas três sub-amostras com a ajuda de rede entomológica e o substrato foi revolvido com os pés. Foram coletados 3601 indivíduos, os quais foram identificados 8 ordens e 41 famílias. Por meio dos índices ambientais foi possível observar que os pontos 1 e 2 possuem excelente qualidade da água e são minimamente afetados pelo turismo, por outro lado os pontos 3 e 4 possuem uma qualidade de água intermediária e são altamente impactados pelo turismo. Três dos quatro feriados estudados mostraram uma diminuição significativa na abundância de insetos após o feriado. A riqueza e a diversidade da fauna de insetos aquáticos não mostraram flutuações sazonais, apesar da ocorrência de diferentes velocidades de vazão durante os períodos seco e chuvoso. Nossos resultados indicaram que os distúrbios causados pelo turismo afetam diretamente na diversidade e abundância dos insetos aquáticos no córrego Sentinela. Além disso, esses insetos se mostraram adequados para a avaliação de impactos antropogênicos causados pelo turismo na conservação de ecossistemas lóticos.